2001
DOI: 10.1002/app.1982
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of elastomeric polyurethane/clay nanocomposites

Abstract: An elastomeric polyurethane/clay (PU/clay) nanocomposite based on poly(propylene glycol) (PPG), glycerol propoxylate, and toluene-diisocyanate (TDI) was synthesized by intercalative polymerization technology. The results of wide angle X-ray diffraction (WAXD) studies showed that the gallery distance of the clay in the hybrid was enlarged from 1.9 to 4.5nm or more. Introducing clay in the PU matrix resulted in an increase in both the tensile strength and elongation at beak. When the clay content reached about 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 7 publications
3
84
1
2
Order By: Relevance
“…However, processing is usually not the focal point of these studies [7][8][9] and normally not investigated systematically. Furthermore, the processing for elastomeric systems tends to be less complex than the more reactive rigid PU systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, processing is usually not the focal point of these studies [7][8][9] and normally not investigated systematically. Furthermore, the processing for elastomeric systems tends to be less complex than the more reactive rigid PU systems.…”
Section: Introductionmentioning
confidence: 99%
“…8 In a previous paper, we reported the use of ultrasound to aid the exfoliation of organically modified montmorillonite (OMMT) in low molar mass poly(propylene glycol). 9 It was shown that in low viscosity media, high shear by itself may not be sufficient to achieve exfoliation.…”
Section: Introductionmentioning
confidence: 99%
“…No espaçamento interplanar d = 1,5 nm, um pico foi observado somente no TPU 10%, provavelmente devido ao excesso de argila nesse compósito, e consequentemente uma pobre dispersão. Em outros dois trabalhos citados na literatura, a dispersão decai com o aumento do teor de argila na matriz polimérica [16,22]. Na Figura 3 são apresentados os resultados de microscopia eletrônica de varredura e de mapeamento do silício, obtido por microanálise por energia dispersiva para as amostras TPU 1% (Figura 3a), TPU-E 3% (Figura 3b) e TPU 10% (Figura 3c).…”
Section: Materiaisunclassified
“…Os compósitos de TPU/nanopartículas podem ser obtidos através de polimerização em massa [7][8][9][10][11][12], polimerização em solução [13], incorporação em extrusora [14,15] e extrusão reativa [16]. De acordo com a literatura, os compósitos de TPU com a argila Cloisite® 30B (C30B) são os que apresentam os melhores resultados com relação às propriedades mecânicas quando comparadas às demais nanopartículas [6-11, 14, 15, 17].…”
Section: Introductionunclassified